2021
DOI: 10.1371/journal.pone.0251331
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and needed reforms in midwifery and nursing regulatory systems in India: Implications for education and practice

Abstract: Background In India, nursing regulation is generally weak, midwifery coexists with nursing, and 88% of nursing and midwifery education is provided by the private health sector. The Indian health system faces major challenges for health care provision due to poor quality, indeterminate regulatory functions and lack of reforms. Methods We undertook a qualitative investigation to understand midwifery and nursing education, and regulatory systems in India, through a review of the regulatory Acts, and an investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…The Council has limitations in human resources and infrastructure and lacks the authority needed to address key issues that directly impact nurses and midwives ( Sharma et al. , 2010 ; Mayra et al. , 2021b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Council has limitations in human resources and infrastructure and lacks the authority needed to address key issues that directly impact nurses and midwives ( Sharma et al. , 2010 ; Mayra et al. , 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2021b ). A recent study reported on the challenges of regulating midwifery scope of education and practice across five Indian states ( Figure 3 ), including a theory and practice mismatch in pre-service education; lack of teachers; medical domination in regulation and governance; lack of infrastructure; lack of leadership; corruption; a complete absence of regulation for private education systems and a lack of practice regulation ( Mayra et al. , 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the management of complaints and disciplinary procedures are also included, as are setting codes of conduct and ethical standards. Hence, the regulatory systems in India, when endorsed, will have implications for education and practice [ 30 ]. This challenging contextual factor has also been identified in other countries in the South-East Asia region (3).…”
Section: Discussionmentioning
confidence: 99%
“…The largest group of studies was associated with regulatory strengthening programs in sub-Saharan African countries (62,131,182,187,190,201,202). There were also studies from Cambodia, India, Nepal and Vietnam (64,203,204). Initiatives to introduce or strengthen accreditation of education programs and institutions were embedded within broader HPR reform programs designed to improve the quality of the health workforce (62,64,201,205).…”
Section: Accreditation Of Health Practitioner Education (Hpe) Programsmentioning
confidence: 99%